What Remains of the Monetarist Counter-Revolution? - Thomas Mayer (University of California, Department of Economics, 1996)
The widespread belief that monetarism has failed is open to question. Certain strong monetarist positions have been damaged by unfolding events, but more moderate propositions live on in current ""Keynesian"" consensus.
Keywords: 330